Interaction motion on pneumatic cylinder using prescribed performance force tracking impedance control - Addie Irawan, Hashim; Mohd Iskandar Putra, Azahar; Zool Hilmi, Ismail (IEEE, 2020)
Pneumatic system has gained popularity in robotics and industrial automation technology especially in developing a cost-effective and highspeed robot/machine with low maintenance. However, control in such systems is very challenging especially that involved compliant and interaction behavior between the system and unknown environment. Therefore, this study has taken initiative to overcome the nonlinearity and uncertainties of pneumatic actuator in interaction of motion by proposed an accurate impedance control with prescribe performance function. The finite-time in prescribe performance is formulated to improve the force tracking between the desired impedance and unknown environment. The comparison study between proposed impedance control with finite-time prescribe performance force tracking shows almost zero steady-state-error, no oscillation at the first contact with environment, stable pressure in chamber and low energy consumption in terms of control input on valve.